2005
DOI: 10.1515/hf.2005.008
|View full text |Cite
|
Sign up to set email alerts
|

The creep of wood destabilized by change in moisture content. Part 2: The creep behaviors of wood during and immediately after adsorption

Abstract: The fluidity of wood remarkably increases during moisture changes. This phenomenon is termed mechano-sorptive creep. The mechanism of mechano-sorptive creep has been studied, including a previous report by our group. Here, creep tests in bending were carried out for wood during and immediately after adsorption of moisture and after a long moisture conditioning. The effects of the rate of moisture adsorption on creep were also examined. The results and conclusions are as follows: (I) Greater creep occurred imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…In conclusion, for the nearly steady-state S 1 , where temperature was lower and RH was constant, V-C strain did not easily recover, whereas, for the non-steadystate S 2 , where temperature was higher and RH and MC varied significantly, V-C strain recovered easier and produced reverse V-C strain. Theoretically, compared with the steady-state, the creep is large for the non-steady-state (Takahashi et al 2004(Takahashi et al , 2005(Takahashi et al , 2006. This is the main cause for the differences in creep between the two schedules.…”
Section: Variation Of V-c Strain Characteristicsmentioning
confidence: 99%
“…In conclusion, for the nearly steady-state S 1 , where temperature was lower and RH was constant, V-C strain did not easily recover, whereas, for the non-steadystate S 2 , where temperature was higher and RH and MC varied significantly, V-C strain recovered easier and produced reverse V-C strain. Theoretically, compared with the steady-state, the creep is large for the non-steady-state (Takahashi et al 2004(Takahashi et al , 2005(Takahashi et al , 2006. This is the main cause for the differences in creep between the two schedules.…”
Section: Variation Of V-c Strain Characteristicsmentioning
confidence: 99%
“…In our previous paper (Takahashi et al 2005) we described findings in relation to point (2). Greater creep occurred in tests under constant MC immediately after rapid adsorption of moisture than after slow adsorption, but the degree of creep during the changing processes was similar, regardless of the changing rate of moisture.…”
Section: Introductionmentioning
confidence: 95%
“…A memory effect of the 0% RH state was apparent, as outlined above. Takahashi et al (2005) reported that samples showed greater stabilization during slower and longer adsorption Brought to you by | University of Queensland -UQ Library Authenticated Download Date | 6/18/15 7:46 AM than in rapid and shorter processes. Accordingly, destabilization and stabilization occur simultaneously during adsorption processes, and the balance between them is affected by the adsorption rate.…”
Section: Influence Of Moisture Conditioning History On Creep During Amentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of investigations concentrated on the experimental determination and analytical expressions of the mechano-sorptive creep (Mukudai and Yata 1988;Hunt 1989;Toratti and Svensson 2000;Navi et al 2002;Takahashi et al 2004Takahashi et al , 2005Takahashi et al , 2006Dong et al 2010;Kaboorani et al 2013;Violaine et al 2015). However, the pure visco elastic creep is usually neglected in numerical models and received much less attention compared to the mechanosorptive effects (Liu 1993).…”
Section: Introductionmentioning
confidence: 99%